Jinendrabuddhi's Viśālāmalavatī Pramāņasamuccayatīkā, Chapter 6 - Muroya, Yasutaka (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
The current volume presents a diplomatic and critical Sanskrit edition of the sixth and final chapter of Jinendrabuddhi's Pramāņasamuccayatīkā, where the focus is the theory of "false rejoinders," a dialectical question rarely treated by Indian Buddhist logicians later than the seventh century.